Harmful algae in the planktonic food web of the Baltic Sea - Uronen, Pauliina (Helsingin yliopisto, 2010)
This study deals with algal species occurring commonly in the Baltic Sea: haptophyte Prymnesium parvum, dinoflagellates Dinophysis acuminata, D. norvegica and D. rotundata, and cyanobacterium Nodularia spumigena. The hypotheses are connected to the toxicity of the species, to the factors determining toxicity, to the consequences of toxicity and to the transfer of toxins in the aquatic food web. Since the Baltic Sea is severely eutrophicated, the fast-growing haptophytes have potential in causing toxic blooms. In our studies, the toxicity (as haemolytic activity) of the haptophyte P. parvum was highest under phosphorus-limited conditions, but the cells were toxic also under nitrogen limitation and under nutrient-balanced growth conditions. The cellular nutrient ratios were tightly related to the toxicity. The stoichiometric flexibility for cellular phosphorus quota was higher than for nitrogen, and nitrogen limitation led to decreased biomass. Negative allelopathic effects on another algae (Rhodomonas salina) could be observed already at low P. parvum cell densities, whereas immediate lysis of R. salina cells occurred at P. parvum cell densities corresponding to natural blooms. Release of dissolved organic carbon from the R. salina cells was measured within 30 minutes, and an increase in bacterial number and biomass was measured within 23 h. Because of the allelopathic effect, formation of a P. parvum bloom may accelerate after a critical cell density is reached and the competing species are eliminated. A P. parvum bloom indirectly stimulates bacterial growth, and alters the functioning of the planktonic food web by increasing the carbon transfer through the microbial loop. Our results were the first reports on DSP toxins in Dinophysis cells in the Gulf of Finland and on PTX-2 in the Baltic Sea. Cellular toxin contents in Dinophysis spp. ranged from 0.2 to 149 pg DTX-1 cell-1 and from 1.6 to 19.9 pg PTX-2 cell-1 in the Gulf of Finland. D. norvegica was found mainly around the thermocline (max. 200 cells L-1), ...